Conversão térmica dos resíduos urbanos como alternativa energética para o encerramento dos lixões da Paraíba - Mélo, Sahyonara Estrela de Lacerda Hussein (2021)
Currently, Brazil has been going through a great challenge, the closure of open-air dumps and their environmentally appropriate destination. In 2020, 79 million tons of waste were generated, with 29.5 million tons of urban solid waste (MSW) ending up in landfills or controlled landfills, which do not have a set of systems and measures necessary to protect the environment. environment and people's health from damage and degradation. In this circumstance, it becomes urgent to search for alternatives to minimize urban solid waste in the world. Municipalities in the state of Paraíba have been facing difficulties in closing activities in dumps, given the large volume of waste deposited and few financial resources to invest in environmentally correct disposal. Many of these dumps are located close to places of human consumption, such as plantations and water resources. In the state of Paraíba, in the year 2018 to 2021, there was a growth of more than 550% of the municipalities that close the dumps, with 156 municipalities out of 223 properly destined. Several studies are carried out to improve the management of solid waste and new forms of treatment, having the energy reuse intrinsic to the minimization of pollution, the recovery of these wastes can come from a pyrolysis process, which has as products composed in the form of gas, liquid and/or solid, and which can be used as an energy source. The methodology used in the study was through the physical-chemical characterization obtained through immediate analysis, analysis of calorific value, X-Ray fluorescence (FRX) and thermogravimetric analysis. The MSW had a percentage of 10% of humidity, having influence by the way in which the material was found, whereas the RO (organic residues) had 71.11%. The result of the immediate analyzes showed that there is a large amount of compounds that can be devolatilized, in addition to that, the values obtained for the calorific value of RO were 20.13 MJ/kg and MSW in 17.82 MJ/kg, being comparable to traditional biomass fuels that have already been used for energy purposes. Through thermogravimetric analysis, it was noted that at 150 °C, moisture loss occurs, which corresponds to the drying process and at around 214 °C, thermal decomposition begins. From the results of the physicochemical characteristics, it is possible to analyze the viability of MSW in the pyrolysis process. Considering that urban solid waste is viable for the pyrolysis process, the authors suggest the microbiological conversion of organic waste. The pyrolysis of municipal waste is an alternative to reduce dependence on foreign energy sources and an incentive to move world consumption from fossil fuels to renewable energies. The objective of this work was to evaluate the potential of application of the pyrolysis process in the treatment of urban solid waste, aiming at the generation of renewable energy.